Congo red dye adsorption using ZnAl layered double hydroxide fabricated using hydrothermal methods - Fitri, Anisa; Lumbanraja, Febriwan Rizki; Hanifah, Istiara Rizqillah; Prasetya, Bayu; Aflaha, Rizky; Putra, Septia Eka Marsha (Green and Sustainable Materials Society, 2024)
Industrial dye pollutants, particularly azo dyes like Congo red, pose significant environmental and health risks due to their toxic and non-biodegradable nature. This study assesses ZnAl Layered Double Hydroxide (ZnAl LDH) as an effective adsorbent, incorporating comprehensive materials characterization and adsorption isotherm analyses. Materials characterization using SEM and XRD confirmed the structural integrity and morphological suitability of ZnAl LDH for dye adsorption. Results demonstrated that ZnAl LDH, particularly the HMTA-based variant (h-ZnAl LDH), achieved superior adsorption capacities of up to 17.8 mg/g, significantly outperforming the urea-based (u-ZnAl LDH) with capacity of 12.3 mg/g. Kinetic analysis showed that the pseudo-second-order (PSO) model provided a better fit (R2 = 0.995) than the pseudo-first-order (PFO) model, indicating that chemisorption plays a dominant role in the adsorption mechanism. The adsorption process was also best described by the Langmuir isotherm model (R2 = 0.989), indicating monolayer adsorption on a homogeneous surface, while the Freundlich model (R2 = 0.944) also provided a reasonable fit, suggesting some degree of multilayer adsorption on heterogeneous surfaces. The superior performance of HMTA-based ZnAl LDH presents a significant advancement in wastewater treatment technologies